MiR-122 Inhibits Cell Proliferation and Tumorigenesis of Breast Cancer by Targeting IGF1R - Wang, Biyun (Public Library of Science, 2012)
miRNAs are emerging as critical regulators in carcinogenesis and tumor progression. Recently, microRNA-122 (miR-122) has been proved to play an important role in hepatocellular carcinoma, but its functions in the context of breast cancer (BC) remain unknown. In this study, we report that miR-122 is commonly downregulated in BC specimens and BC cell lines with important functional consequences. Overexpression of miR-122 not only dramatically suppressed cell proliferation, colony formation by inducing G1-phase cell-cycle arrest in vitro, but also reduced tumorigenicity in vivo. We then screened and identified a novel miR-122 target, insulin-like growth factor 1 receptor (IGF1R), and it was further confirmed by luciferase assay. Overexpression of miR-122 would specifically and markedly reduce its expression. Similar to the restoring miR-122 expression, IGF1R downregulation suppressed cell growth and cell-cycle progression, whereas IGF1R overexpression rescued the suppressive effect of miR-122. To identify the mechanisms, we investigated the Akt/mTOR/p70S6K pathway and found that the expression of Akt, mTOR and p70S6K were suppressed, whereas re-expression of IGF1R which did not contain the 3′UTR totally reversed the inhibition of Akt/mTOR/p70S6K signal pathway profile. We also identified a novel, putative miR-122 target gene, PI3CG, a member of PI3K family, which further suggests miR-122 may be a key regulator of the PI3K/Akt pathway. In clinical specimens, IGF1R was widely overexpressed and its mRNA levels were inversely correlated with miR-122 expression. Taken together, our results demonstrate that miR-122 functions as a tumor suppressor and plays an important role in inhibiting the tumorigenesis through targeting IGF1R and regulating PI3K/Akt/mTOR/p70S6K pathway. Given these, miR-122 may serve as a novel therapeutic or diagnostic/prognostic-target for treating BC.